THE RECONSTRUCTION OF LEGAL AID LAW FOR CHILDREN WHO GETCONFLICT WITH LAW IN PROCESS OF JUSTIFICATION FOR CHILDRENBASED ON THE VALUE OF PANCASILA - Adi Mansar; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Indonesia country is a constitutional  which is coming from the law number three/ MPR / 2000 about the law an the order of rules of law. Chapter 28D verse one stated “everyone has a right in testimonial, guarantee, protection, and the law which must be fair and have the same treatment in law. Constitution has given the guarantee that all of society, will not be treated discriminatively and forbid the human right based on the chapter 28 verse 2 stated “everyone has a right to be free from the discriminated action and get the protection for the  discriminative things.  Pancasila as the ideology and the rules of social live in Indonesia has become a priority with the vision to guarantee the process of life and nation character, in order all of Indonesian society has aright to get law protection, therefore the little children.  Some helps from law for children who get conflict with law, the treatment be difference with adults, children have no ability to protect their own right, many side convince their live, the country and society have importance to protect children. Based on the abstract above , so the problem study is formulated below : 1. How the setting of legal aid the children who have conflict with law in the process of children law is positive right now? 2. How is the application of legal aid the children who have the conflict with law is positive nowadays? 3. How is the reconstruction of legal aid for children who have the conflict with the law in process of legalization for children based on the value of  Pancasila? Based an Soerjono Soekanto, the base of theory is using paradigm. Where the paradigm is divided in two three kind, they are : 1. Paradigm means law, 2.) paradigm differenciate law, 3.) paradigm as the laws order sector. The kind of research is a sociological yuridis law research or empirical yurudis. According to kirk and miller, the qualitative research is a certain tradition in social science fundamentally depended on the observation of human in the region and term. According to sugiyono the method of qualitative is suitable to be used in the research which the problem is unclean, and it is being done in the narrow social situation, so the result of this research will be deeper. According to Soerjono Soekanto the qualitative  approach is actually the research which result is descriptive.  The research uses the social legal research approach, tamahana states that socio-legal studied is given to law and society studies. Based on F.X. Adji samekto, social legal studies form the law as norm and reality, researcher in socio legal studies demand the controller of law which have been built in the knowledge of law it self ( as the apriory law and unlimited of values), and the domination of how theories work. As the consequen which look at as a reality.  The location of research is in Medan city (the court of law grade 1A, Medan, the office of public prosecutor, resort police office medan, PERADI). This research uses the primary data and secondary data and the object of tertiery law.  The technique of data collecting has been done by observation and interview with the key informan whom have been decided by researcher based on the charasteristic of research. To get the accurate data, it needs sampling distribution and random decision whether it is simple and more difficult.  The respondents whom will be asked are law practitioner and advocates, policeman, lawyer, public prosecutor. Meanwhile the collecting of secondary data, is being done by library research (documentation) that is a chronological way to find out the data by reading, analyzing, classifying and being done by the understanding of law as reflected in rules, the literature which is relevant with the problems.  The technique of analysis with the primary data, the researcher uses the technique of data analysis and type is strauss and J.Corbin, by analyzing the data since the researcher was in the field. Then  the researcher arranges the category of the data in term on theme. After the data has been given the validation, the researcher did the reconstruction and analysis with the qualitative inductive to answer the problem.  The technique of validation has a purpose to know the validity of data which has been got in the research. The technique which is used is triangulation for the source, they are : 1. By comparing the data which has been taken from observation with the data which has been taken form the result of interview with the informant. 2. By doing the comparison between perception, point of view and general opinion and the opinion research. 3. By comparing the result of interview with library research after the triangulation process done. The researcher will decide the valid data which will be used as a material for research.  The grand theory which is used in this dissertation is the theory of justice. 1. John Rawls theory about justice.  Based on john rawls in the book of “ a theory of justice “ explains the theory of social  condition as the difference principl, is the social difference and economy must be settled to give a benefit for them who are not lucky. The term of social economy different in the different principal to answer. The difference in prospect of someone to get the element of welfare income and authority. Meanwhile the principal of fair equality of opportunity shows them who have low chance to achieve the prospect of wealth, authority and income. Themselves must be given the special protection. 2. John Stuart Mill’s Justice Theory  Based on john stuart mill’s idea of utilitarianism, there are two kinds. They are happiness and truth. Mill stated the happiness and the truth as the assumption which the base of thinking about justice based on utilitarian perspective. Mill stated the purpose of life is the happiness and there is no pain, but mill stated that the justice is not sui generis because depended on functions. Mills approach through the justice is placed in analysis about logics and morality sense, started from the unfair things in society and it build is the universal concept to analyze it. Mills stated the justice theory which is separated from the function prosecution. 3. The theory of Pancasila justice  Pancasila is the philosophy for Indonesian country and laws of 1945 is source of law for all of rules of Indonesian laws. Laws manage every single life is element in a nation. So the justice can be built continuously and it has purpose for country to achieve welfare of society. One of nation purpose is to create the justice for everyone, that thing consist in the second part and fifth in pancasila. As well as can be seen in the principal of thought in UUD NRI 1945 and country is willing to create the social justice for all of people in Indonesia. 4. The theory of restorative  The restorative justice is a form of justice which is centered for the need of victim, the criminals and society. The approach of restorative justice is a paradigm to be used as a strategy and frame in handling crime problems which answer the dissatisfaction of justice system of criminal nowadays. The restorative approach is assumed as the changing of model and mechanism which work in the justice system in handling the problems of criminal nowadays. The middle theory is the system law theory of Lawrence M. Friedman. As a system, friedman divides the system of law into the three element, they are: a. Legal structure, b. Legal substance, c. Legal culture. Friedman states the law can not be straighten if there is no credible law upholder, competent and also independent. The weak of mentality in laws upholder cause the inability to straight up the law as well. The dissertation applied theory uses the progressive theory, the concept of progressive law was born and developing from the dissatisfaction feeling from the expert of law through the theory and traditional law practice which develop and criticize the asymmetrical between law and theory ( law in books) with the law in action, and the failure from law in giving the respon through the problems which happened in society. The progressive law is started from the basic assumption, law is the institution which has a purpose to transport the human in to the balance life, wealth and make the human get the happiness. Law it self does not reflect the law as the absolute and final, but is decided by it is ability to serve human. Characteristic of progressive law based on satjipto rahardjo is : law is presented to serve the society. a.) progressive law will be still exist because the law will always be on it is position as the law in the making and will not be final as long as human present, so the progressive law will always be exist to arrange to life of society. b.) in progressive law, the ethnic and humanity moral will be very strong, which will give the respon for the developing and human needs and serve the justice and wealth.  The process of green table of children who have conflict with law in the civil court of law based on the reguirement of chapter 5 2/ till chapter 62 laws numb 11, 2012 about the system of  Crime Judicature. In the court of law, ist class in Medan, the process of green table for children who hare the conflikt with law based on the reguiremen of law is the laws numb 11, 2012 about system of crime judicature of children and KUHAP.